PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS INKUIRI TERBIMBING TERINTEGRASI SAINTIFIK SERTA PENGARUHNYA TERHADAP HASIL BELAJAR KOGNITIF DAN KETERAMPILAN PROSES SAINS PADA SISWA KELAS XI SMA NEGERI 3 HALMAHERA SELATAN - Mus Samad; Ade Haerullah; Dharmawaty M Taher (Universitas Khairun, 2021)
The purpose of this study was (1) to determine whether the scientifically integrated guided inquiry-based Biology learning device that was developed could be declared feasible to be used in class XI biology learning at SMA Negeri 3 Halmahera Selatan (2) to determine the effect of the scientifically integrated Guided Inquiry learning model on learning outcomes. cognitive skills in class XI SMA Negeri 3 South Halmahera (3) to determine the effect of the scientifically integrated Guided Inquiry learning model on science process skills in class XI students at SMA Negeri 3 Halmahera Selatan. This research is a research development or Research and Development (R&D). The sample of this study consisted of two classes, namely XI IPA-1 as an experimental class and Class XI IPA-2 as a control class with 36 students. The instrument used was an essay test for science process skills and for cognitive learning outcomes in the form of a multiple choice test (PG). ). Analysis of the data using data analysis of the feasibility of learning devices and normality test, homogeneity assisted by SPSS while hypothesis testing using the Anacova test. The results showed that (1) the -based Biology Learning Toolkit The scientifically integrated guided inquiry developed in class XI of SMA Negeri 3 South Halmahera with a value of 92.7% is categorized as suitable for use (2) there is an influence of the scientifically integrated guided inquiry learning model on cognitive learning outcomes in class XI students of SMA Negeri 3 Halmahera Selatan with a value level significant 0.03> 0.05 (3) there is an effect of scientifically integrated Guided Inquiry Learning Model on science process skills in class XI students of SMA Negeri 3 Halmahera Selatan with a significant value of 0.01> 0.05.